Local Application of Semaphorin 3A Combined with Adipose-Derived Stem Cell Sheet and Anorganic Bovine Bone Granules Enhances Bone Regeneration in Type 2 Diabetes Mellitus Rats - Xiaoru Xu; Kaixiu Fang; Lifeng Wang; Xiangwei Liu; Yuchao Zhou; Yingliang Song (Stem Cells International)
Bone tissue regeneration is considered to be the optimal solution for bone loss. However, diabetic patients have a greater risk of poor bone healing or bone grafting failure than nondiabetics. The purpose of this study was to investigate the influence of the complexes of an adipose-derived stem cell sheet (ASC sheet) and Bio-Oss® bone granules on bone healing in type 2 diabetes mellitus (T2DM) rats with the addition of semaphorin 3A (Sema3A). The rat ASC sheets showed stronger osteogenic ability than ASCs in vitro, as indicated by the extracellular matrix mineralization and the expression of osteogenesis-related genes at mRNA level. An ASC sheet combined with Bio-Oss® bone granules promoted bone formation in T2DM rats as indicated by microcomputed tomography (micro-CT) and histological analysis. In addition, Sema3A promoted the osteogenic differentiation of ASC sheets in vitro and local injection of Sema3A promoted T2DM rats’ calvarial bone regeneration based on ASC sheet and Bio-Oss® bone granule complex treatment. In conclusion, the local injection of Sema3A and the complexes of ASC sheet and Bio-Oss® bone granules could promote osseous healing and are potentially useful to improve bone healing for T2DM patients.